2015
DOI: 10.1021/acs.jpcb.5b08941
|View full text |Cite
|
Sign up to set email alerts
|

Distortions of the Xanthophylls Caused by Interactions with Neighboring Pigments and the LHCII Protein Are Crucial for Studying Energy Transfer Pathways within the Complex

Abstract: It has been proposed that photoprotective non-photochemical quenching (NPQ) in higher plants arises from a conformational change in the antenna which alters pigment-pigment interactions. This brings about the formation of energy quenching "traps" that capture and dissipate excitation energy as heat. We have used the semiempirical AM1-CAS-CI method combined with the transition density cube (TDC) approach to model chlorophyll (Chl) to xanthophyll (Xanth) resonant Coulomb couplings in the crystal structure of LHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…This state must be lower in energy than the Chls and/or possess a higher coupling with them. This last condition might derive from an increased dipole character of the S q ←S 0 transition due to a higher degree of twisting of the Car 40 . The heterogeneity in the population rates of S q from the Chls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This state must be lower in energy than the Chls and/or possess a higher coupling with them. This last condition might derive from an increased dipole character of the S q ←S 0 transition due to a higher degree of twisting of the Car 40 . The heterogeneity in the population rates of S q from the Chls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since the Chl c pigments in FCP have a ∼35-nm blue-shifted Q y transition compared with Chl a (17) and transfer excitation energy to Chl a on an ultrafast timescale (37), they do not contribute directly to the lowest-energy excitons in FCP. In LHCII, the lowest-energy excitons are localized on Chls a610, a611, a612, a602, and a603 7, and the close vicinity of xanthophylls to these sites (23) results in strong interactions between these xanthophylls and Chls a610, a611, a612, and a603 (38), while Chl a602 is also affected through its strong coupling with a603. However, since transient absorption spectra of FCP do not show evidence of energy transfer from Fx to Chl c (16,17), we can rule out Chl c's participation in FCP's lowest-energy exciton states.…”
Section: Discussionmentioning
confidence: 99%
“…Xanthophylls have been the continued focus of the search for the ‘true quencher’ of excess energy in the photosynthetic membrane. The role of lutein has been the focus of recent research, most recently with Duffy and co-workers ( Fox et al, 2015 ) have shown through modeling that the degrees of distortions of lutein are more important than the pigments location for quenching in the membrane. Here we addressed and quantified the photoprotective capacities of xanthophylls in vivo for the first time.…”
Section: Discussionmentioning
confidence: 99%